ASSESSING SOCIO-ECONOMIC JUSTICE RIGHTS THROUGH ZAKAT FOR COMMUNITIES AFFECTED BY COVID-19 - Zainuddin Zainuddin; Salle Salle (Universitas Syiah Kuala, 2023)
Covid-19 has had a significant economic impact, reducing people's purchasing power in community. The concept of zakat as an instrument for fulfilling the socioeconomic rights of the Islamic community become questionable in this situation. This normative legal research uses a conceptual and statutory approach, with descriptive-qualitative analysis. Zakat is one of the Islamic instruments for the fulfillment of the social and economic justice, in particular for development projects, education services, health services when meet the criteria for becoming a recipient of zakat. Therefore, zakat is a simple transfer of a certain sized portion of the wealth of the rich to the poor. The rights of the poor are an essential right in zakat because God has confirmed that in one's wealth and income. The distribution of zakat to communities affected by COVID-19 for the fulfillment of socioeconomic justice rights is carried out through a health emergency program, which involves health and curative programs, and an economic emergency program, which includes strengthening food security and people's purchasing power. It is confirmed that Zakat has contributed to ensure the economic justice during Covid-19